PUSAT REHABILITASI GANGGUAN JIWA DAN SKIZOFRENIA DENGAN PENDEKATAN ARSITEKTUR PERILAKU DI KABUPATEN KULONPROGO - Annisa Mutia Sari; Musyawaroh Musyawaroh; Wiwik Setyaningsih (ARSITEKTURA, 2017)
Abstract: Psychiatric disorder sufferers in Indonesia is increasing every year. This also happens in the Daerah Istimewa Yogyakarta which is the province with the largest number of psychiatric sufferers in Indonesia. The phenomenon of the increasing psychiatric sufferers  happen due to the lack of mental health services and facilities so that many sufferers of psychiatric disorders that have not been handled properly. The problem that arise in the design of Psychiatric Disorder and Schizophrenia Rehabilitation Center is how to create the design of rehabilitation center that accomodates the activities and needs of sufferers both physically and mentally based on behavior that indicated the sufferers. The goal is to get the container activities and needs that play a role in the healing of sufferers psychologically, socially, and spiritually with Behaviorism Architecture as the design concept. The methods used in the design of Psychiatric Disorder and Schizophrenia Rehabilitation Center is Behaviorism Concept. This concept was applied in architectural elements focused on three aspects, namely, privacy, comfort, and security. The application of the Behaviorism concept aims to meet the appropriate design in accordance with the surferrers’ behavior wihich is realized through optimization of potential site and the zonning concept. The basic form of the building is a square shape in combination with pyramid roof and sloping roof to get a homey impression. Likewise, the look of the building is made simple, but it capable to display the principles of Behaviorism Architecture. Kata kunci: Behavior Architecture, Psychiatric Disorders, Rehabilitation Center, Schizophrenia